Research on the interstellar medium and star formation in the Galaxy: An Indian perspective - Mookerjea B.; Maheswar G.; Acharyya K.; Baug T.; Datta P.; Jose J.; Ojha D.K.; Pandian J.D.; Roy N.; Samal M.; Sharma S.; Soam A.; Vig S.; Das A.; Dewangan L.; Dutta S.; Eswariah C.; Majumdar L.; Mallick K.K.; Mondal S.; Ninan J.P.; Panwar N.; Pathak A.; Rastogi S.; Sahu D.; Tej A.; Veena V.S. (My University, 2025)
Although the star-formation process has been studied for decades, many important aspects of the physics involved remain unsolved. Recent advancements in instrumentation in the infrared, far-infrared, and sub-millimeter-wavelength regimes have contributed to a significantly improved understanding of processes in the interstellar medium (ISM) leading to star formation. The future of research on the ISM and star formation looks exciting with instruments like the JWST, ALMA, etc., already contributing to the topic by gathering high-resolution high-sensitivity data and with several larger ground- and space-bound facilities either being planned or constructed. India has a sizable number of astronomers engaged in research on topics related to the ISM and star formation. In this white paper invited by the Astronomical Society of India to prepare a vision document for Indian astronomy, we review the Indian contributions to the global understanding of the star-formation process and suggest areas that require focused efforts both in creating observing facilities and in the theoretical front in India, to improve the impact of our research in the coming decades. © Indian Academy of Sciences 2024.